Straightforward Selection of Broadly Neutralizing Single-Domain Antibodies Targeting the Conserved CD4 and Coreceptor Binding Sites of HIV-1 gp120 - Matz, Julie (American Society for Microbiology, 2013)
Few broadly neutralizing antibodies targeting determinants of the HIV-1 surface envelope glycoprotein (gp120) involved in sequential binding to host CD4 and chemokine receptors have been characterized. While these epitopes show low diversity among various isolates, HIV-1 employs many strategies to evade humoral immune response toward these sensitive sites, including a carbohydrate shield, low accessibility to these buried cavities, and conformational masking. Using trimeric gp140, free or bound to a CD4 mimic, as immunogens in llamas, we selected a panel of broadly neutralizing single-domain antibodies (sdAbs) that bind to either the CD4 or the coreceptor binding site (CD4BS and CoRBS, respectively). When analyzed as monomers or as homo- or heteromultimers, the best sdAb candidates could not only neutralize viruses carrying subtype B envelopes, corresponding to the Env molecule used for immunization and selection, but were also efficient in neutralizing a broad panel of envelopes from subtypes A, C, G, CRF01_AE, and CRF02_AG, including tier 3 viruses. Interestingly, sdAb multimers exhibited a broader neutralizing activity spectrum than the parental sdAb monomers. The extreme stability and high recombinant production yield combined with their broad neutralization capacity make these sdAbs new potential microbicide candidates for HIV-1 transmission prevention.